Advancing Religious Moderation: Policies and Practices in Indonesian State Islamic Universities - Anica Anica; Abdullah Idi; Fajri Ismail; Muh Mawangir (STAI Hubbulwathan Duri, 2025)
This study assesses the effectiveness of education policies promoting religious moderation using the Countenance Stake Model. Religious moderation in education policy research encompasses what researchers analyze and the desired outcomes sought by stakeholders, ensuring scientific accountability. The research employed a qualitative approach to evaluate religious moderation programs at Raden Fatah State Islamic University Palembang and Raden Intan State Islamic University Lampung. Data collection included document analysis, interviews, and observations, focusing on the implementation and outcomes of religious moderation initiatives. Findings reveal the reinforcement of religious moderation within the educational framework of State Islamic Universities (PTKIN). Programs such as the revitalization of Academic Culture and Student Affairs (PBAK) activities have successfully aligned with the universities' core objectives, promoting education and teaching rooted in moderation. Training and activities conducted by the universities played a significant role in fostering this initiative. This research highlights the critical role of state Islamic universities in mainstreaming religious moderation. By implementing structured programs and aligning with the Ministry of Religion's policies, these institutions have effectively integrated moderation into academic and extracurricular frameworks. The study underscores the effectiveness of religious moderation policies at Raden Fatah and Raden Intan State Islamic Universities. These efforts contribute significantly to the broader goal of embedding moderation within the educational and societal context.